2022
DOI: 10.1038/s41524-022-00846-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure factors and the importance of adsorbate effects in chemisorption on surface alloys

Abstract: The chemisorption energy is an integral aspect of surface chemistry, central to numerous fields such as catalysis, corrosion, and nanotechnology. Electronic-structure-based methods such as the Newns-Anderson model are therefore of great importance in guiding the engineering of material surfaces with optimal properties. However, existing methods are inadequate for interpreting complex, multi-metallic systems. Herein, we introduce a physics-based chemisorption model for alloyed transition metal surfaces employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 93 publications
0
43
0
Order By: Relevance
“…These variations can, to first order, be described by a shift of the upper band edge of the d-states, as discussed elsewhere, 69 with a second-order correction based on the d-band filling of the neighboring atoms. 70 Figure 3 shows that the 𝐵𝐸 ̅̅̅̅ 𝑀 of monometallic Pt 9-9-9 is ~2.2 eV too negative compared to the volcano peak. Alloying Pt with, e.g., Au, however, results in less negative 𝐵𝐸 ̅̅̅̅ 𝑀 , thus shifting the ensemble closer to the volcano peak.…”
Section: Site Stability As Descriptor For Local Volcano Plots and Kin...mentioning
confidence: 94%
See 2 more Smart Citations
“…These variations can, to first order, be described by a shift of the upper band edge of the d-states, as discussed elsewhere, 69 with a second-order correction based on the d-band filling of the neighboring atoms. 70 Figure 3 shows that the 𝐵𝐸 ̅̅̅̅ 𝑀 of monometallic Pt 9-9-9 is ~2.2 eV too negative compared to the volcano peak. Alloying Pt with, e.g., Au, however, results in less negative 𝐵𝐸 ̅̅̅̅ 𝑀 , thus shifting the ensemble closer to the volcano peak.…”
Section: Site Stability As Descriptor For Local Volcano Plots and Kin...mentioning
confidence: 94%
“…This is corrected to second order by the d-band filling of the neighboring atoms reflecting the ability of the surroundings to adopt to perturbations induced by the Pt site. 70 The volcano peak corresponding to the highest possible turnover for an active site is not reached for any of the alloying systems, which all remain on the low 𝐵𝐸 ̅̅̅̅ 𝑀 leg.…”
Section: Site Stability As Descriptor For Local Volcano Plots and Kin...mentioning
confidence: 96%
See 1 more Smart Citation
“…Although the d-band model has shown great success in understanding catalytic performance over a few decades, there are known limitations. For example, SAAs and the related class of near surface alloys (NSAs) can both escape the trends expected from the d-band model (9)(10)(11)(12). Recent developments have shown that NSAs follow stability rules and require corrections to the d-band model to fully describe their properties (9,13).…”
mentioning
confidence: 99%
“…For example, SAAs and the related class of near surface alloys (NSAs) can both escape the trends expected from the d-band model (9)(10)(11)(12). Recent developments have shown that NSAs follow stability rules and require corrections to the d-band model to fully describe their properties (9,13). But such an approach is not applicable to SAAs.…”
mentioning
confidence: 99%